Reducing Organizational Anomie in Light of Entrepreneurial Behavior - Azeez, Lamees Adnan; Hasson, Shiffa Mohamed Ali (Journal of Economics and Administrative Sciences, 2021)
The research aims to clarify the role of the main variable represented by the four dimensions of entrepreneurial behavior (creative, risk-taking, seizing opportunities, proactivity), in Reducing the dependent variable of organizational anomie with the dimensions (Organizational Normlessness, Organizational Cynicism, Organizational Valuelessness).The experimental, analytical method was adopted in the completion of the research, and an intentional sample of (162) individuals in the administrative levels (higher and middle) in the factory was taken. The questionnaire was also adopted as the main tool, which included (54) paragraphs, as (162) forms were distributed and 144 were retrieved from them, valid for statistical analysis from the total forms distributed to the factory.The most important results of the research showed the effect of the dimensions of entrepreneurial behavior and directly on organizational anomie, and that the relationship of entrepreneurial behavior and at the total level was positive with organizational anomie. They ignore the values ​​of work to achieve their goals, as well as the existence of a spirit of cooperation and one team among workers in the factory